Efficacy of curcumin-mediated antibacterial photodynamic therapy for oral antisepsis: A systematic review and network meta-analysis of randomized clinical trials - Ferrisse, Túlio Morandin [UNESP]; Dias, Luana Mendonça [UNESP]; Oliveira, Analú Barros de [UNESP]; Jordão, Claudia Carolina [UNESP]; Mima, Ewerton Garcia de Oliveira [UNESP]; Pavarina, Ana Cláudia [UNESP] (Elsevier, 2022)
Background: The presence of oral microorganisms resistant to traditional treatment is increasing, thus a search for new therapies is needed. In this context, antimicrobial photodynamic therapy (aPDT) is an approach for the treatment of antibiotic resistant andnon resistant microorganisms. Therefore, the aim of the present study was to conduct a systematic review and meta-analysis of randomized clinical trials of aPDT for oral antisepsis against oral polymicrobial biofilms. Methods: PubMed, Science Direct, Scopus, SciELO, Lilacs, Cochrane Library and Embase databases were searched. In total, five articles were included for qualitative analysis and four articles were used for quantitative analyses. Bias assessment of the eligible articles was made using the RoB 2 criteria. Network meta-analysis was performed using the random-effect model. Subgroup's analysis was also conducted. The groups evaluated were aPDT, exposure to light only and no treatment at all (control group). The quality of evidence was assessed by CINeMA approach. Results: aPDT mediated by curcumin had significant results in the reducing bacterial load (0.31–0.49 log10 UFC/ I2=0%) when compared with the control group. The included articles were classified as low risk of bias, despite biases detected by allocation and blinding. Moreover, quantitative analysis between aPDT and control group and between light and control group were classified with low risk of confidence rating, while the results from aPDT versus light were classified as moderate risk of confidence rating. Conclusion: aPDT has significant efficacy for oral antisepsis, however more randomized clinical trials will be needed to validate the present results.
Keywords: Antimicrobial photodynamic therapy; Network meta-analysis; Oral microorganism; Oral polymicrobial biofilm; Photodynamic therapy; Systematic review